Tropical Medicine and Leishmaniasis: Unraveling the Complexities of a Neglected Tropical Disease - Shruti Morankar (International Journal of Tropical Medicines, 2024)
Protozoan parasites of the genus Leishmania are the cause of the vector-borne disease leishmaniasis, which poses a serious threat to global public health in tropical and subtropical areas. Despite being common and having a significant effect on human health, leishmaniasis is still a neglected tropical disease, with little funding available for investigation and prevention. This article examines the relationship between leishmaniasis and tropical medicine, emphasizing the particular difficulties this intricate illness presents and the continuous efforts to treat it. With its emphasis on illnesses common in tropical areas, tropical medicine offers an essential foundation for comprehending the pathophysiology, epidemiology, and treatment of leishmaniasis. Even with these developments, leishmaniasis detection and treatment still face difficulties, especially in areas with low resources where the illness is most prevalent. Disease control is still hampered by a lack of access to reliable diagnostic instruments and efficient therapies, which emphasizes the necessity of ongoing funding for research and development. In conclusion, there is a rare chance to address the intricacies of this neglected tropical illness thanks to the convergence of research on leishmaniasis and tropical medicine. Through the utilization of interdisciplinary techniques and cooperative endeavours, we can progress our comprehension of leishmaniasis and formulate inventive approaches for managing and eradicating the disease, consequently enhancing the welfare and health of impacted communities.
Keywords: Protozoan; epidemiology; leishmania; neglected tropical illness; tropical medicine; vector-borne diseases